Are clinical and functional results of MIPPO and IMN for treatment of extraarticular distal tibia fractures similar? - Taskesen, Anil; Ugur Yaradilmis, Yuksel; Ozdemir, Mahmut; Sesen, Hakan; Demirkale, Ismail; Altay, Murat (Annals of Medical Research, 2021)
None